UTILIZATION OF HERBALS AND THEIR FORMULATION IN SIDDHA TREATMENT FOR VARIOUS TYPES OF DISEASES - T.B, EKNATH BABU; SUBISH.R; SARANYA.H; KOHILA.G; SUNDARANANTHAVALLI.S (Innovare Journal of Ayurvedic Sciences, 2016)
Abstract Alternative medicine is any practice that is put forward as having the healing effects ofÂ medicineÂ but is not based onÂ evidenceÂ gathered using the scientific method. Herbalism "herbology"Â orÂ "herbal medicine" is use of plants for medicinal purposes, and the study of such use. Plants have been the basis for medical treatments through much of human history, and suchÂ traditional medicineÂ is still widely practiced today. Modern medicine recognizes herbalism as a form ofÂ alternative medicine, as the practice of herbalism is not strictly based onÂ evidenceÂ gathered using theÂ scientific method. The scope of herbal medicine is sometimes extended to includeÂ fungalÂ andÂ beeÂ products, as well asÂ minerals,Â shellsÂ and certain animal parts. Naturopathy is based on vitalism, which posits that a special energy called vital energy or vital force guides bodily processes such asÂ metabolism,Â reproduction, growth, and adaptation. We have meet several siddha vaithiyars, and collected information about their treatment, the herbals used in the preparation of various formulations used to cure several diseases. Siddha vaidhiyas gave information of the treatment for various diseases. They are acute, chronic and common diseases. Thus we make awareness about the preparation of siddha formulations so, that it is easy to treat the various diseases without complication.